Transforming Telecoms in Afghanistan : Expanding Affordable Access by Introducing Competition - Bhatia, Bhavna (World Bank, Washington, DC, 2012)
Afghanistan has transformed its telecommunications from a fragmented system serving few people to a modern one putting Afghans in touch with one another and with the global economy. The government moved quickly to approve a Telecommunications and Internet Policy in 2003, and identified telecommunications as one of the two lead sectors for attracting private and foreign investment. The experience in Afghanistan shows that wireless communications can play a critical role as the primary telecommunications infrastructure in a post-conflict country. The key factors in Afghanistan's success in developing its telecommunications sector have been strong government commitment, a pro-competitive reform agenda, early focus on regulatory reforms and capacity building, and a transparent bidding process.